Bullying in con/flating spaces: why a ‘space’ perspective matters for understanding young people's expiriences and practices of bullying - Bork-Hüffer, Tabea; Mahlknecht, Belinda; Kaufmann, Katja (AoIR2020, 2020)
There is an urgent need for the currently mostly disparate and quantitative research on traditional or cyberbullying, to not only take note of each other, but also to analyse the interdependences, intersections and conflation of bullying in digital and offline spaces in a more comprehensive manner. More recent conceptualisations of ‘space’ offer valuable contributions to a reflection upon the epistemological and related methodological considerations when seeking to understand the lifeworlds, practices and experiences of young people involved in bullying. In this sense, we have recently advanced the concept of “cON/FFlating situational spaces and places” (Bork-Hüffer and Yeoh 2017: 93) in an attempt to integrate existing algorithmic, (post-)feminist and relational perspectives to the analysis of bullying (cf. Bork-Hüffer et al. 2020). We ask: Whether and how does bullying in physical and digital spaces intersect in school contexts? We applied narratives produced by young people themselves in Austria with the objective to let them speak with their own voice when describing their experiences and involvement with (cyber)bullying. Even when bullying practices themselves seemed to be restricted to digital spaces, they are still entangled within the spatialities of participants’ relations, practices, identities and life-worlds that stretch across inseparable socio-material and technological spheres. The results reflect how the ontogenesis of socio-technological developments shapes the opportunities for, types of, frequencies and harshness of bullying attacks.
Gesehen am 08.05.2025